(untitled) (Economics and region, 2020)
Based on the study of the state of Ukrainian enterprises and peculiarities of the world’s leading companies growth, the main tasks for improving quality of project and multi-project management of domestic enterprises modernization (improvement) and development of their high-tech production systems were identified. A modern model (standard) of turnkey formation and implementation of innovation and investment mechanism (projects and target programs) of continuous-cyclical process of creating science-intensive competitive products with a high level of added value and systems of its high-tech production at domestic enterprises was proposed by authors. In article was considered world management standards, the latest achievements of advanced science and technology, modern theory of strategic, multi-project, corporate and innovation and production management. The basic procedures and tools for the formation, organization and management of turnkey implementation of unique innovation and investment projects and targeted programs for the development of high-tech research and production systems and powerful enterprises in Ukraine were determined. The key steps and main stages of design and program activities to improve investment, innovation and production and economic mechanisms of the enterprise have been developed. A set of practical measures for effective program-targeted and project management of continuous innovation-economic and high-tech development of domestic products and their producers, covering all phases and stages of the life cycle of relevant programs and projects were proposed. Implementation of the proposed mechanisms and procedures of multi-project management of innovation and economic development will help increase the competitiveness of Ukrainian producers, ensure their faster transition to world standards of management and development, and ultimately – increase the welfare of Ukraine.